PUBLIC AWARENESS ABOUT SYMPTOMS AND PREVENTION OF COVID-19 IN BENOWO, SURABAYA - Dwi Wahyu Indriati; Diyantoro Diyantoro; Anita Kurniati; Aliyah Siti Sundari; Rizka Oktarianti Ainun Jariah; Nur Septia Handayani (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Since its first report, COVID-19 has remained a major threat worldwide. Various attempts were made to treat and prevent further transmission of COVID-19. In Indonesia, although the first case was reported nearly five months after the first case in Wuhan, the transmission was the fastest among Southeast Asian countries. Several efforts have been made to prevent further transmission. Objective: Our community services program aimed to assess the public understanding of COVID-19 symptoms and the application of SHE (Self and Environmental Health) as a form of COVID-19 prevention. Method: We conducted counseling using a door-to-door method to increase the understanding of SHE as a form of COVID-19 prevention and then at the end of the visit, a questionnaire was given to measure the understanding of symptoms and prevention COVID-19 transmission. Results: After conducted the door-to-door counselling in Kandangan district, it is known that the public understanding of the symptoms and ways of preventing COVID-19 is quite good. The method of prevention that is understood by the public includes using masks, diligently wash hands, and maintain social distance in gathering. However, there are still people who do not understand (31.13%) that increasing their immune system by consuming nutritious and balanced food and exercise can also be used to prevent the transmission of COVID-19. Because a good immune system can prevent individuals from infection with pathogens such as COVID-19. Conclusion: The community has sufficient understanding of the symptoms and ways of preventing COVID-19 so that it is expected it can reduce the transmission of COVID-19 in Benowo District, Surabaya.